Soil Microbiomes With the Genetic Capacity for Atmospheric Chemosynthesis Are Widespread Across the Poles and Are Associated With Moisture, Carbon, and Nitrogen Limitation - Ray, Angelique E.; Zhang, Eden; Terauds, Aleks; Ji, Mukan; Kong, Weidong; Ferrari, Belinda C. (Frontiers in Microbiology, 2020)
Soil microbiomes within oligotrophic cold deserts are extraordinarily diverse. Increasingly, oligotrophic sites with low levels of phototrophic primary producers are reported, leading researchers to question their carbon and energy sources. A novel microbial carbon fixation process termed atmospheric chemosynthesis recently filled this gap as it was shown to be supporting primary production at two Eastern Antarctic deserts. Atmospheric chemosynthesis uses energy liberated from the oxidation of atmospheric hydrogen to drive the Calvin-Benson-Bassham (CBB) cycle through a new chemotrophic form of RuBisCO, designated IE. Here, we propose that the genetic determinants of this process; RuBisCO type IE (rbcL1E) and high affinity group 1h-[NiFe]-hydrogenase (hhyL) are widespread across cold desert soils and that this process is linked to dry, nutrient-poor environments. We use qPCR to quantify these genes in 122 soil microbiomes across the three poles; spanning the Tibetan Plateau, 10 Antarctic and three high Arctic sites. Both genes were ubiquitous, being present at variable abundances in all 122 polar soils examined (rbcL1E; 6.25×10^3- 1.66×10^9 copies/g soil, hhyL; 6.84×10^3- 5.07×10^8 copies/g soil). For the Antarctic and Arctic sites, random forest and correlation analysis against 26 measured soil physiochemical parameters revealed that rbcL1E and hhyL genes were associated with lower soil moisture, carbon and nitrogen content. While further studies are required to quantify the rates of trace gas carbon fixation and the organisms involved, we highlight the global potential of desert soil microbiomes to be supported by this new minimalistic mode of carbon fixation, particularly throughout dry oligotrophic environments, which encompass more than 35% of the Earth’s surface.